2018
DOI: 10.1186/s40880-018-0319-7
|View full text |Cite
|
Sign up to set email alerts
|

Phenformin alone or combined with gefitinib inhibits bladder cancer via AMPK and EGFR pathways

Abstract: BackgroundIn previous studies, we have shown that the combination of metformin and gefitinib inhibits the growth of bladder cancer cells. Here we examined whether the metformin analogue phenformin, either used alone or in combination with gefitinib, could inhibit growth of bladder cancer cells.MethodsThe growth-inhibitory effects of phenformin and gefitinib were tested in one murine and two human bladder cancer cell lines using MTT and clonogenic assays. Effects on cell migration were assessed in a wound heali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 34 publications
4
17
0
1
Order By: Relevance
“…e abnormal glycosylated protein is polyubiquitinated and transferred from the ER into the cytoplasm, and then this abnormal glycosylated PD-L1 gets degraded by proteasome [25]. Consistent with the previous study [11] which showed that the phosphorylation of PD-L1 was associated with ER glycosylation, Chan et al reported that PD-L1 phosphorylation recruits STT3A, an ER-associated glycosyltransferase, to catalyze PD-L1 glycosylation and maintain PD-L1 stability [15]. Hsu and colleagues reported that epithelial-mesenchymal transition (EMT) induced N-glycosyltransferase STT3 through β-catenin, and subsequent STT3-dependent PD-L1 N-glycosylation stabilizes and upregulates PD-L1 [26].…”
Section: Glycosylationsupporting
confidence: 90%
See 1 more Smart Citation
“…e abnormal glycosylated protein is polyubiquitinated and transferred from the ER into the cytoplasm, and then this abnormal glycosylated PD-L1 gets degraded by proteasome [25]. Consistent with the previous study [11] which showed that the phosphorylation of PD-L1 was associated with ER glycosylation, Chan et al reported that PD-L1 phosphorylation recruits STT3A, an ER-associated glycosyltransferase, to catalyze PD-L1 glycosylation and maintain PD-L1 stability [15]. Hsu and colleagues reported that epithelial-mesenchymal transition (EMT) induced N-glycosyltransferase STT3 through β-catenin, and subsequent STT3-dependent PD-L1 N-glycosylation stabilizes and upregulates PD-L1 [26].…”
Section: Glycosylationsupporting
confidence: 90%
“…Phosphorylation is the most widely studied PTM, and its crosstalk with other PTMs has been significantly proved in recent studies [10]. Metformin activates the AMP-activated protein kinase (AMPK), and then S195 of PD-L1 is directly phosphorylated by p-AMPK, which induces the abnormal glycosylation of PD-L1, leading to its endoplasmic reticulum (ER) accumulation and ER-associated degradation [11]. is process of protein degradation is called endoplasmic reticulum-associated degradation (ERAD) [12].…”
Section: Phosphorylationmentioning
confidence: 99%
“…AMPK‐dependent signaling has been shown to mediate the effects of metformin and phenformin on cell growth. In bladder cancer, especially, metformin or phenformin and gefinitib, a well‐known EGFR tyrosine kinase inhibitor, cooperated to inhibit cell growth via AMPK and EGFR pathways . However, this mechanism was not active in our system; indeed, metformin and phenformin did not alter the expression of AMPK‐related molecules (data not shown).…”
Section: Discussionmentioning
confidence: 74%
“…Among them, metformin is a potential anti-tumor drug that inhibits hepatic gluconeogenesis and can exert its effects via activation of AMPK [190]. Additionally, the metformin analogue phenformin, alone or in combination with gefitinib, inhibits bladder cancer growth via AMPK activation and EGFR signaling inhibition [191].…”
Section: Glutaminolysismentioning
confidence: 99%